Peningkatan Penguasaan Materi Kependudukan Melalui Pembelajaran Jigsaw - Wartana Wartana (Universitas Muhammadiyah Surakarta, 2016)
This study aimed to describe the learning outcome with the subject matter of Population Social Science Approach Jigsaw. Subjects and data sources eighth grade students study VIII F as many as 36 students. Methods of data collection using observation, documentation, and testing. Analysis of data using a critical and comparative analysis. Indicators of success using the criteria limit minimal is 75 and the target completeness 100%. Research procedure uses cycles. Based on the resultt of research and discussion can be concluded that: the data obtained from pre cycle until the second cycle, obtained the progress of student achievement in the learning of Social Sciences with the material of the population through the approach of Jigsaw, the pre cycle average of 73 and the first cycle an average of 79 and the second cycle by an average of 87. from this data, it seems clear that an increase in the average value of pre cycle to a first cycle of six figures (8%), from the first cycle to the second cycle an increase of 8 numbers (10%) , from the second cycle pre cycle to an increase of 14 points (19%). The highest value pre cycle stage at 82 and 88 as well as the first cycle of the second cycle of 92. It is clear that from the stage to the first cycle pre cycle an increase of 6 numbers (7%), from the first cycle to the second cycle an increase of 6 numbers (7% ), and the second cycle of pre cycle to an increase of 12 points (14%). The lowest scores were obtained for 66 pre cycle stage and the first cycle of 72 and the second cycle of 82. thus, can be affirmed that the step of the first cycle pre cycle to an increase of 6 figures (9%), from the first cycle to the second cycle an increase of 10 number (14%), and the second cycle of pre cycle to an increase of 16 points (24%). The percentage of mastery learning from pre cycle obtained by 29% and the first cycle was obtained by 70% and the second cycle of 100%. It seems clear that from the stage to the first cycle pre cycle an increase of 41%, from the first cycle to the second cycle an increase of 30%, and from the second cycle pre cycle to an increase of 71%. Thus, the learning achievements of students in Social Sciences with a population of matter through Jigsaw from pre cycle approach to the second cycle there is a significant rise